(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to analyze the role of halaqoh mufradat in the development of maharah al-kalam of Ma’had Al-Bir students. Halaqoh mufradat is one of the flagship programs that focuses on mastering Arabic vocabulary as the foundation of speaking skills. This study uses a qualitative approach with a descriptive method. Data collection techniques include observation of halaqoh activities, interviews with musyrifah and female students, and documentation of learning programs. The results of the study show that halaqoh mufradat plays a significant role in improving students’ speaking skills, especially in the aspects of fluency, accuracy of vocabulary use, and the courage to communicate orally. Through the habit of memorizing mufradat, practicing dialogue, and applying vocabulary in the context of daily ma’had, female students are more active in using Arabic communicatively. In addition, a conducive halaqoh atmosphere and intensive assistance from the musyrifah also support the effectiveness of this program. Thus, halaqoh mufradat can be used as an effective learning model in developing maharah al-kalam in a ma’had-based educational environment.